1993
DOI: 10.1159/000236407
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Loratadine on Late Phase Reaction Induced by Conjunctival Provocation Test

Abstract: The protective effect of Loratadine, a new generation, non-sedating antihistamine, on clinical and cellular events during the early phase reaction (EPR) and late phase reaction (LPR) of the allergen-specific conjunctival provocation test (CPT) was assessed out of the pollen season in 20 seasonally allergic rhino-conjunctivitis patients. After a screening CPT, selected patients were randomized to Loratadine (10 mg OD) or matching placebo for 7 days. CPT was repeated following treatment. Clinical and cellular re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…The method is easy to perform, low-priced, rarely elicits systemic reactions and is also independent of the examiner's experience and the patient's compliance [10,11,14,15]. The CPT makes it possible to assess the therapeutic (pharmacological) effect on the severity of allergic reactions [16], determine optimal treatment doses in immunotherapeutic dose-finding studies and define the current status of a patient's allergic severity. For patients with pronounced conjunctivitis, one can objectify the treatment results or the current allergy status using digital image processing when the reddening of the challenged eyes is documented with high-resolution photos.…”
Section: Introductionmentioning
confidence: 99%
“…The method is easy to perform, low-priced, rarely elicits systemic reactions and is also independent of the examiner's experience and the patient's compliance [10,11,14,15]. The CPT makes it possible to assess the therapeutic (pharmacological) effect on the severity of allergic reactions [16], determine optimal treatment doses in immunotherapeutic dose-finding studies and define the current status of a patient's allergic severity. For patients with pronounced conjunctivitis, one can objectify the treatment results or the current allergy status using digital image processing when the reddening of the challenged eyes is documented with high-resolution photos.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally easy to perform, inexpensive, rarely associated with systemic reactions, and largely independent of the patient's compliance and examiner's experience [7,20,22,60]. It is considered as an approved tool for analyzing pathomechanisms of allergic diseases and assessment of pharmaceutical effects on the allergic reaction [61]. …”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that marked infiltrations of eosinophils and neutrophils into conjunctival tissue were seen in patients with allergic conjunctivitis [25][26][27][28]. However, different from the intraperitoneally sensitised guinea pigs, neutrophils but not eosinophils migrated outside the conjunctiva of the topically sensitised animals.…”
Section: Discussionmentioning
confidence: 89%